Monomeric Fe(iii) half-sandwich complexes [Cp′FeX2] – synthesis, properties and electronic structure. Issue 31 (20th June 2018) - Reiners, Matthias; Maekawa, Miyuki; Baabe, Dirk; Zaretzke, Marc-Kevin; Schweyen, Peter; Daniliuc, Constantin G.; Freytag, Matthias; Raeder, Jan; Hohenberger, Johannes; Sutter, Jörg; Meyer, Karsten; Walter, Marc D.
Abstract : Bis(alkyl)iron(iii ) half-sandwich complexes exhibit solvent dependent reactivity when treated with H2 . Abstract : The half-sandwich complex [Cp′Fe(μ-I)]2 (1 ; Cp′ = η 5 -1, 2, 4-(Me3 C)3 C5 H2 ) is cleaved when heated in toluene to form a cation–anion pair [{Cp′Fe(η 6 -toluene)} + Cp′FeI2 − ] (2 ), in which the two Fe(ii ) atoms adopt different spin states, i.e., a low-spin ( S = 0) and a high-spin ( S = 2) configuration. Upon oxidation of1 with C2 H4 I2, the thermally stable 15VE species [Cp′FeI2 ] (3 ) can be isolated, in which the Fe(iii ) atom adopts an intermediate spin ( S = 3/2) configuration. Complex3 is an excellent starting material for further functionalizations and it reacts with Mg(CH2 SiMe3 )2 to form the unprecedented Fe(iii ) ( S = 3/2) bis(alkyl) complex [Cp′Fe(CH2 SiMe3 )2 ] (4 ). The respective spin states of complexes2–4 are confirmed by single-crystal X-ray crystallography, zero-field 57 Fe Mössbauer spectroscopy, and solid-state magnetic susceptibility measurements. In contrast to the related 14VE high-spin ( S = 2) Fe(ii ) alkyl species [Cp′FeCH(SiMe3 )2 ], which resists the reaction with H2 as a consequence of a spin-induced reaction barrier, complex4 reacts cleanly with H2 (8 bar) in cyclohexane to yield iron hydrides [{Cp′Fe}2 (μ-H)3 ] (5 ) and [Cp′Fe(μ-H)2 ]2 (6 ) in a 1 : 4 ratio. However, when the hydrogenation of4 is carried out in benzene, a green 19VE [Cp′Fe(η 6 -C6 H6 )] (A ) intermediate is formed, which dimerizes to the bis(cyclohexadienyl)-bridged product [(Cp′Fe)2 (μ2 –η 5 :η 5 -C12 H12 )] (7 ). Further evidence for the intermediacy of [Cp′Fe(η 6 -C6 H6 )] (A ) was gathered by X-band EPR and UV/vis spectroscopy. Interestingly, attempts to oxidize7 with AgSbF6 proceeded via C–C bond cleavage instead of metal oxidation to form [Cp′Fe(C6 H6 )][SbF6 ] (8 ).